PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR BEAT OLEH KONSUMEN DI PT.KENCANA MULIA ABADI TELUKDALAM - Josep Rijal Wau (Jurnal Ilmiah Mahasiswa Nias Selatan, 2025)
The aim of this research is to determine the influence of pricing and marketing on purchasing choices for Beat motorbikes from PT. Kencana Mulia Abadi Telukdalam. This is referred to as associative quantitative research. The population of this study consisted of all PT. Kencana Mulia Abadi Telukdalam customers, with a total sample of 40 respondents taken using an Accidental Sampling approach. The data collection strategy for this research is by distributing questionnaires to respondents. The analytical method used is multiple linear analysis. Based on the findings of this research, the price variable (X1) and the promotion variable (X2) both have quite a large influence on customer purchasing choices To increase the value of purchasing decisions at PT. Kencana Mulia Abadi Telukdalam, it is necessary to evaluate competitor prices and ensure that the prices set are competitive and commensurate with the value of the product; able to identify added value that can be provided to consumers. For example, improving or adding features, warranties or after-sales services to increase product value; develop a more successful advertising approach that focuses on product benefits. For example, the use of digital platforms and social media to increase reach and interaction with consumers; increasing employee training in sales communications to ensure sales staff have adequate product knowledge and can provide convincing information to prospective buyers; and develop an informative online platform or website about beat motorbikes, including features, specifications and customer reviews. Apart from conducting educational programs to increase consumer knowledge regarding the benefits and advantages of products, providing product demo trials to potential consumers, as well as designing effective pricing and advertising methods to stimulate decision making regarding beat motorbikes.